2009
DOI: 10.1007/s10461-009-9546-x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Antiretroviral Adherence in HIV+ Ugandan Parents and Their Children Initiating HAART in the MTCT-Plus Family Treatment Model: Role of Depression in Declining Adherence Over Time

Abstract: We conducted a study to assess the effect of family-based treatment on adherence amongst HIV-infected parents and their HIV-infected children attending the Mother-To-Child-Transmission Plus program in Kampala, Uganda. Adherence was assessed using home-based pill counts and self-report. Mean adherence was over 94%. Depression was associated with incomplete adherence on multivariable analysis. Adherence declined over time. Qualitative interviews revealed lack of transportation money, stigma, clinical response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
101
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(107 citation statements)
references
References 44 publications
4
101
2
Order By: Relevance
“…Earlier studies from varying regional settings have identified psychological distress as a barrier to optimal adherence. 46,47 Further in-depth studies in this patient population are needed to understand the impact of psychological function on treatment adherence, and psychosocial interventions (e.g., cognitive behavioral therapy) should be examined. 48 Having sex is an important part of overall health and quality of life, including patients infected with HIV.…”
Section: Venkatesh Et Almentioning
confidence: 99%
“…Earlier studies from varying regional settings have identified psychological distress as a barrier to optimal adherence. 46,47 Further in-depth studies in this patient population are needed to understand the impact of psychological function on treatment adherence, and psychosocial interventions (e.g., cognitive behavioral therapy) should be examined. 48 Having sex is an important part of overall health and quality of life, including patients infected with HIV.…”
Section: Venkatesh Et Almentioning
confidence: 99%
“…10 A Ugandan study showed that adherence to ART declined over time and that factors such as lack of transportation and money, stigma, clinical response to therapy, drug packaging and cost may impact on adherence. 11 Long-term viral suppression requires consistent and high percentage adherence accompanied by optimal inter-dose intervals. Efforts to improve viral outcomes should address not only missed doses but wide variations in dose timing.…”
Section: Introductionmentioning
confidence: 99%
“…21 HIV increases the risk of developing major depression through a variety of mechanisms including: direct injury to subcortical areas of the brain; chronic stress; stigmatization; worsening social isolation; bereavement; debilitation; and intense demoralization. 22 Research suggests that co-morbid depression in patients with HIV/AIDS may be associated with reduced adherence to ART 11,[23][24][25][26][27] and furthermore with disease progression. 28,29 A study in Ethiopia found that patients who were not depressed were two times more likely to be adherent than those who were depressed, although the principal reasons given for skipping doses were simply forgetting, feeling ill, being busy and running out of medication.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, one can take all doses in a timely fashion without persisting with the regimen for the entire prescribed duration of treatment. Second, studies of adherence to pharmacological treatment for chronic illnesses have documented declining dose-taking execution 22 and persistence 23 over time, and this bodes poorly for the long-term success of treatment scale-up for persons with uncurable but manageable chronic illnesses who face a lifetime of pill-taking. Third, depending on the pharmacokinetic properties of the specific medication under consideration, a high degree of punctuality in average dose-taking execution can still result in poor outcomes if the rare episodes of non-persistence (described variously as drug holidays, 9 treatment interruptions, 24 or non-permissible gaps 10 ) are sequentially concentrated in time.…”
mentioning
confidence: 99%